MEMAHAMI POTENSI POSITIVE SELF-TALK SEBAGAI ALAT DALAM KONSELING PASTORAL: ANALISIS STUDI KUALITATIF - David Eko Setiawan (Institut Agama Kristen Negeri Manado, 2023)
The technique of positive positive self-talk is often used as one of the methods in counseling to help clients overcome their emotional and spiritual problems. This research aims to evaluate the effectiveness of positive self-talk technique as a tool in pastoral counseling using the library research method and data analysis through content analysis. This study involves an analysis of the literature related to positive self-talk technique and pastoral counseling and conducting content analysis of the collected data to evaluate the effectiveness of positive positive self-talk technique as a tool in pastoral counseling. The results of the research show that positive positive self-talk technique is effective in helping clients overcome their emotional and spiritual problems and has great potential as a tool in pastoral counseling. The implication of these findings is that positive positive self-talk technique can be effectively used by pastoral counselors to help their clients overcome their problems and achieve a better self-understanding.